Dehydration and digestibility in vitro of coffee pulp silage - Ramón Ferrer, José; Páez, Gisela; Chirinos, Miguel (Rev. Téc. Fac. Ing. Univ. Zulia)
A study of coffee pulp dehydration process was carried out in silos, to observe the main pulp components effects on their digestibility in vitro. Thu pulp was dried in a open yar and daily measurements of absolute humidity percentage, relative humidity percentage and wet bulb temperature were performed. Digestibility percentage in vitro was also determined by means of an enzymatic extract of Trichoderma reesei QM 9414 cellulasa wich was added to ensilaged coffee pulp and lignocellulosic coffee pulp samples. Other substracts used were tanin-cellulose and caffeine-cellulose mixtures. Coffee pulp enzymatic activity was determined by using the filter paper technique. The results obtained indicate that digestibility of ensilaged coffee pulp is directly proportional to its caffeine and tanine content. Conversely, the higher the lignin content in coffee pulp, the lower its digestibility. As polymeric compound, lignin well know by its obstructing action on cellulose hydrolysis. Dehydration of the ensilaged coffee pulp, on the other hand, is a fast process when humidity is lowered to an 8.4% for a two days and 17 hours sun exposure span.